Using cryoprobes of different sizes combined with cone-beam computed tomography-derived augmented fluoroscopy and endobronchial ultrasound to diagnose peripheral pulmonary lesions: a propensity-matched study - Ching-Kai Lin; Sheng-Yuan Ruan; Hung-Jen Fan; Hao-Chun Chang; Yen-Ting Lin; Chao-Chi Ho (Respiratory Research, 2024)
Abstract Background Endobronchial ultrasound (EBUS) and cone-beam computed tomography-derived augmented fluoroscopy (CBCT-AF) are utilized for the diagnosis of peripheral pulmonary lesions (PPLs). Combining them with transbronchial cryobiopsy (TBC) can provide sufficient tissue for genetic analysis. However, cryoprobes of different sizes have varying degrees of flexibility, which can affect their ability to access the target bronchus and potentially impact the accuracy. The aim of this study was to compare the diagnostic efficacy of cryoprobes of varying sizes in CBCT-AF and EBUS for the diagnosis of PPLs. Methods Patients who underwent endobronchial ultrasound-guided transbronchial biopsy (EBUS-TBB) and TBC combined with CBCT-AF for PPLs diagnosis between January 2021 and May 2022 were included. Propensity score matching and competing-risks regression were utilized for data analysis. Primary outcome was the diagnostic accuracy of TBC. Results A total of 284 patients underwent TBC, with 172 using a 1.7-mm cryoprobe (1.7 group) and 112 using a 1.1-mm cryoprobe (1.1 group). Finally, we included 99 paired patients following propensity score matching. The diagnostic accuracy of TBC was higher in the 1.1 group (80.8% vs. 69.7%, P = 0.050), with a similar rate of complications. Subgroup analysis also revealed that the 1.1 group had better accuracy when PPLs were located in the upper lobe (85.2% vs. 66.1%, P = 0.020), when PPLs were smaller than 20 mm (78.8% vs. 48.8%, P = 0.008), and when intra-procedural CBCT was needed to be used (79.5% vs. 42.3%, P = 0.001). TBC obtained larger specimens than TBB in both groups. There is still a trend of larger sample size obtained in the 1.7 group, but there is no statistically different between our two study groups (40.8 mm2 vs. 22.0 mm2, P = 0.283). Conclusions The combination of TBC with CBCT-AF and EBUS is effective in diagnosing PPLs, and a thin cryoprobe is preferred when the PPLs located in difficult areas.